Design and Research on the Variable Polar Distance of the Double-Sided Linear Induction Motor for Electromagnetic Catapult - Xijun Liu; Hao Zhao; Houlong Ai; Zelin Chen (Energies)
According to the special technical requirements of carrier-based aircraft catapults, this paper describes the design of a variable pole distance bilateral linear induction motor. When the traditional constant pole motor is used as the catapult of carrier-based aircraft, the current frequency continues to increase during the catapult process, which greatly aggravates the burden of the motor. Therefore, we propose a variable pole length primary double-sided linear induction motor structure. Compared with the traditional constant pole motor structure, this structure can gradually increase the pole distance with an increase in speed when the current frequency remains unchanged. In contrast, the variable pole distance method with a current frequency of 200 Hz has a pole distance of 0.262 m when the displacement is 10 m, and the pole distance increases to 0.352 m when the displacement is 100 m. By maintaining a constant current frequency, this method effectively reduces the control complexity at high speed. Through the theoretical analysis and research calculation conducted on the designed motor, a finite element simulation model was also established by ANSYS 14.0, and the influence of the change in the pole distance on the performance of the motor was analyzed. The magnetic field line and magnetic density distribution of the motor are simulated and analyzed, and the validity of the theoretical calculation is verified.